Effects of reduced kinematic and social play experience on affective appraisal of human-rat play in rats - Liu, Quanxiao; Ilčíková, Tereza; Radchenko, Mariia; Junková, Markéta; Špinka, Marek (Frontiers in zoology, 2023)
BACKGROUND: Play is a common and developmentally important behaviour in young mammals. Specifically in Norway rats (Rattus norvegicus), reduced opportunity to engage in rough-and-tumble (RT) play has been associated with impaired development in social competence. However, RT play is a complex behaviour having both a kinematic aspect (i.e., performing complex 3D manoeuvres during play fights) and a social aspect (interacting with a playful partner). There has been little research so far on disentangling the two aspects in RT play, especially on how these two aspects affect the affective appraisal of the intense physical contact during play. RESULTS: To examine the developmental effects of kinematic and social play reduction on affective appraisal in rats, we subjected male Long-Evans rats from 21 days old to RT play experience that was reduced either kinematically (through playing in a low ceiling environment) or socially (through playing with a less playful Fischer-344 rat). Starting at 35 days, we measured their production of positively (50-kHz) and negatively (22-kHz) valenced ultrasonic vocalisations (USVs) in a 2-min standardised human-rat play procedure that mimicked the playful sequences of nape contact, pinning, and belly stimulation ('tickling') for ten days. We hypothesised that the rats with kinematically or socially reduced play would perceive the 'tickling' less positively and thus emit positive ultrasonic vocalisations at lower rates compared to control rats with non-reduced play experience. Our results confirmed that each of the treatments reduced play differently: while the kinematic reduction abolished playful pinnings entirely, the social reduction decreased the pinnings and made play highly asymmetric. During the tickling procedure, rats mostly produced 50 kHz USV, indicating that they appraised the procedure as positive. There was a wide inter individual variance and high individual consistency in rats' USV responses to 'tickling'. Crucially, neither the kinematically nor the socially reduced play experience affected either type of USV production when rats were 'tickled'. CONCLUSIONS: This finding indicates that the ability to appraise play-like interactions as positive remains unaffected even when the kinematic or the social aspect of play experience was substantially curtailed.
Keywords: Ultrasonic vocalisation; Kinematic play; Affective appraisal; Human-rat play; Norway rat; Social play; Animal development; Animal play